Pemberdayaan Petani Milenial: Peluang Pertanian Sebagai Karier Masa Depan - Kusmiati (CV. SINAR HOWUHOWU, 2025)
Empowering millennial farmers is a strategic solution to address the challenges of farmer regeneration in Indonesia and to develop agriculture as a promising future career. This study examines the motivations, utilization of digital technology, and government program support in empowering young farmers. A qualitative case study method was used to explore the experiences and challenges faced by millennial farmers in several regions. The results show that the use of modern technology and entrepreneurship training programs enhance the productivity and competitiveness of millennial farmers. However, limited access to capital and negative societal perceptions remain major obstacles. Synergy among government, private sector, and farming communities is essential to create a sustainable and attractive agricultural ecosystem for the younger generation. These findings are expected to serve as a basis for effective and sustainable policies to empower millennial farmers.